Reproduction potential of Nigerian Meloidogyne spp. and the response of six commercial watermelon cultivars to predominant species - Bello, T.T.; Coyne, D.; Fourie, H. (Springer, 2021)
The reproduction potential of nine single-species Meloidogyne populations and 16 mixed-species communities, recovered from watermelon rhizospheres in South-West Nigeria, were determined in roots of tomato (cv. Tropimech) in a glasshouse. The host responses of six commercial watermelon cultivars were also assessed under glasshouse conditions to single-species populations of Meloidogyne incognita, M. javanica and M. enterolobii. Reproduction potential of different Meloidogyne populations and the host response of the cultivars were assessed based on the number of egg masses, final nematode population (Pf), reproduction factor (Rf) and relative susceptibility values (S%). No significant interaction (P < 0.05) existed between replicated reproduction potential experiments for Meloidogyne populations, while a significant interaction (P < 0.05) was apparent between the two host status experiments. Rfs varied in between 4 and 46 in comparing single and mixed community populations of Meloidogyne spp. All watermelon cultivars were susceptible to the predominant single-species populations of Meloidogyne spp.: ‘Charleston Gray’ had the highest Rf (14.7) for M. enterolobii, while ‘Sugar Dragon’ had the lowest (2.1) for M. incognita. The results suggest that cultivars with the lowest Rf and S% for the respective Meloidogyne spp. should be the preferred choice of producers to avoid uncontrolled population build-up of Meloidogyne spp. The data generated from this study provide valuable and useful information to watermelon growers and breeders focusing on root-knot nematode resistance breeding to enable sustainable cultivation of the crop.